Juridical Analysis of Customary Land Disputes and Their Resolution through Mediation in North Lombok Regency - Syahroni, Muhammad; Susilawati, Rina; Izhar, Muhammad (Justicia Insight, 2025)
Customary land disputes are recurring issues in various regions, including North Lombok Regency, which is rich in local wisdom and customary legal values. This study aims to analyze the juridical aspects of customary land disputes and examine the effectiveness of their resolution through mediation. The research employs a normative and empirical juridical approach by reviewing relevant legislation and conducting interviews with key stakeholders, such as traditional leaders, community members, and law enforcement officials. The findings reveal that resolving customary land disputes through mediation offers a more equitable and sustainable solution, as it accommodates local wisdom and community aspirations. However, challenges remain in implementation, including the lack of synergy between customary and positive law, as well as the limited capacity of mediators to fully understand local customary contexts. Therefore, strengthening regulations and institutional capacity is essential to promote more effective and just resolutions of customary land disputes.